(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Since the inception of mankind man has been striving continuously to evolve, transform and change. Along with them their habitat too has undergone radical changes from primitive to rural and from town to cities. As a process of change, Urbanisation has worked as a catalyst for Modernization. But for the very process of Urbanisation itself economic and non-economic factors have contributed largely. With the ever increasing attraction towards city life for better education, health, jobs and other facilities a number of grave problems have arisen ranging from heavy density of population to squatter settlement and pollution. With more people coming in and increasing rate of employees than employment, this has resulted in unemployment and urban poverty. To mitigate all such problems it becomes imperative to develop villages and provide city like facilities to curb migration and demotivate urbanisation. The situation is already at an alarming stage for Indian Cities and if not taken seriously the conditions of the cities will become more complex and beyond control.